1 Studying the Determinants of Successful Aging: Diet, Lifestyle, and Social Relations in Egypt - Shaltout, Fayrouz (AUC Knowledge Fountain, 2025)
Abstract Background The global population is aging rapidly, with projections indicating that by 2050, one in six people will be over the age of 65. In Egypt, the aging population, particularly those aged 60 and above, is expected to grow significantly, posing a growing public health concern. Unhealthful diets (that are associated with overweight and obesity), are one of the main reasons associated with non-communicable diseases (e.g., diabetes and cardiovascular diseases) are major risk factors for poor aging outcomes. Despite this, there is limited research on the specific determinants of successful aging (SA) in Egypt, especially among individuals aged 50 to 70. This study aims to address this gap by exploring the role of diet, lifestyle, and social relations on successful aging, and identify key SA predictors in Egypt. Methods A cross-sectional survey design was used with 303 participants aged 50 to 70 years in Egypt. Data was collected on demographic, socio-economic, and health-related factors, including marital status, education, occupational status, housing conditions, chronic diseases, physical activity, and dietary habits. A research framework was developed based on data from the literature review, and was used to create the research design, in which both qualitative and quantitative data were collected. SA was measured using the Successful Aging Score (SAS). Statistical analyses, including multi-regression models, were performed to identify significant predictors of SA and their relationships. Results Provide comprehensive insights into the demographic, socio-economic, and health-related characteristics, highlighting how these factors significantly influence health outcomes. Key factors influencing health outcomes included marital status, occupational status, illness days, educational attainment, and other socio-economic factors. The SAS scores showed an inverse relationship with health, indicating that lower SAS scores reflected better health outcomes. Multi-regression analysis identified 7 significant predictors of SA — city of birth, marital status, education, occupation, housing condition, chronic diseases, and dietary habits; healthier dietary patterns were linked to improved aging outcomes. Conclusion To the best of our knowledge, this study is the first to examine these three determinants of successful aging in Egypt, focusing on diet, lifestyle, and social relations. 7 key predictors of SA were identified as interrelated factors contributing to better aging outcomes. These findings emphasize that successful aging is shaped by socio-economic, lifestyle, and possibly other factors, underscoring the need for targeted interventions to enhance the health and well-being of older adults in Egypt. Keywords Successful Aging, Egypt, diet, lifestyle, social relations.